Vaginal hysterectomy in the treatment of genital prolapse. Campbell technique modified - Bedoya, Mariano G. (1964)
The treatment of choice is surgical genital prolapse and no doubt that the best route is vaginal . Only in exceptional cases are used for orthopedic procedures. S gynecologists agree not limit treatment to the use of a single technique . My personal experience allows me to reaffirm this concept . Consequently, the choice of technique is subject to clinical considerations of each case . The age and general condition of the patient , the variety of prolapse and associated injuries are printed guidance factors in the evaluation of surgical procedures . Thus, in the pre -menopausal or menopausal patients with total prolapse , who lost any chance of a normal replacement , and / or associated injuries, and / or when the only way to address the structures that will serve to make plastic required its removal , I recommend vaginal hysterectomy technique advocated by AD Campbell.